If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (10x + 6) + (12 + -4x) = 0 Reorder the terms: (6 + 10x) + (12 + -4x) = 0 Remove parenthesis around (6 + 10x) 6 + 10x + (12 + -4x) = 0 Remove parenthesis around (12 + -4x) 6 + 10x + 12 + -4x = 0 Reorder the terms: 6 + 12 + 10x + -4x = 0 Combine like terms: 6 + 12 = 18 18 + 10x + -4x = 0 Combine like terms: 10x + -4x = 6x 18 + 6x = 0 Solving 18 + 6x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + 6x = 0 + -18 Combine like terms: 18 + -18 = 0 0 + 6x = 0 + -18 6x = 0 + -18 Combine like terms: 0 + -18 = -18 6x = -18 Divide each side by '6'. x = -3 Simplifying x = -3
| 3x-(5x+10)=6 | | 2^x*(16-2^3x/8)=0 | | 5(r-1)=2(1-r) | | 5+2=310 | | 3cos^2(x)-8cos(x)+4=0 | | 0.60*x=96 | | 4x^2+3x+7x^2-x-5x^2= | | 4-4(k-5)=2(2-k)6 | | 6(0)-6y=12 | | x*0.1=200 | | y/4x20/x | | 3/8*9/11 | | 5k-8=3 | | 4x+9=6x-x | | 8x-(2x+5)=5x+(3x-8) | | x-4/5=7 | | 27x^2-27x-35=0 | | (3/8)/9/11 | | (25-2x)(20-2x)(x)= | | y^2*(2.9-y)-1.25=0 | | 16/4x(4)= | | 3-2x=11+2x | | 24=6*b*(1/2) | | 24=6b/2 | | 2a+1/2=3a-1/4 | | 3x^6+9x^4-30x^2=0 | | 7x+1y=80000 | | (16/81)3/4 | | 2cos^2x+3sinx+3=0 | | Y/-12=-36 | | (1-3i)*(5-2zi)=(2i-3)*(3z+2i) | | 3x-(1/7)x=120 |